Management of bakanae disease using induced resistance and QTL for resistance breeding - Puyam, Anita; Pannu, Pushpinder Pal Singh; Bisht, Sunaina (Journal of Cereal Research, 2019)
Rice is one of the most commonly grown cereal crops throughout the world. A number of diseases like blast, brown spot, bacterial leaf blight, false smut and bakanae (foot rot) challenge its production. Presently, bakanae disease has become one of the most important disease of rice in Asia, especially in Punjab region of India where basmati is grown. Management of this disease is difficult and few resistance sources against the disease have been discovered. The standard methods for managing the disease using chemicals have to be checked from time to time due to the probability of resistance development in the pathogen. The present era calls for novel and persistent mechanism to control the disease like Quantitative Trait Loci (QTL) mapping for resistance breeding and using regulatory components of induced resistance. This review elaborates the recent advancement in managing this disease.DOI:https://doi.org/10.25174/2249-4065/2019/95790